Evaluation of MR-neurography in diagnosis and treatment in peripheral nerve surgery of the upper extremity: a matched cohort study - Böcker, Arne Hendrik; Lukhaup, Lara Saskia; Aman, Martin; Bergmeister, Konstantin D.; Schwarz, Daniel; Bendszus, Martin; Kneser, Ulrich; Harhaus-Wähner, Leila (Microsurgery, 2022)
Introduction “Watch and wait”-strategies from 3 to 6 months for peripheral nerve injuries are standard of care in specialized centers. However, this contradiction between delayed decision-making and the demand for fast reinnervation, especially of the motoric endplate, has not yet been overcome. Therefore, this study aimed to investigate the time-sparing effects by accelerated decision-making due to the complementary MR-neurography application combined with established diagnostics like electroneurography and neurosonography from the first admission to the determination of the treatment plan. Patients and Methods A retrospective matched-pair chart review analysis with Supplementary MR-neurography in the period between 2014 and 2017 was designed. Matching was performed by the parameters of nerve type, localization of the nerve injury, patient age, and treatment of the injury. Twenty-nine patients were included and matched in the study. MR-neurography imaging was performed by a 3T magnetic resonance imaging with a sampling perfection with application optimized contrasts using different flip angle evolution short tau inversion recovery sequence for the brachial plexus and gradient echo accurate fast imaging with steady-state free precession sequence for the upper extremity. Time to decision-making was investigated for or against a surgical intervention for patients with or without a Supplementary MR-neurography. Results In general, MR-neurography accelerated decision-making for 28 days, with results of 37.5 + 5.4 days with Supplementary MR-neurography and 65.3 + 9.7 days without Supplementary MR-neurography (p = .05). Within the first 90 days following trauma, patients with MR-neurography (38.2 ± 7.7 days) benefit under a significant faster decision-making (p = .05) than patients without MR-neurography (79.0 + 14.2 days). After 90 days, no evidence of accelerated decision-making was found with the addition of MR-neurography (p = .6). In 10 of the 29 patients, despite additional electroneurography and neurosonography, no decision could be made and the MR-neurography has been used primarily as a diagnostic tool. Conclusion MR-neurography has significant time-sparing effects on the decision-making for approximately 4 weeks within the first 90 days after the trauma. This may help overcome the paradigm of “watch and wait”-strategies during the first 3-6 months after the peripheral nerve injury.
Online veröffentlicht: 21. Dezember 2021
Gesehen am 01.10.2025